Molecular epidemiology and clinical characteristics of respiratory syncytial virus in hospitalized children during winter 2021–2022 in Bengbu, China - Huang, Limin; Xu, Yuanyou; Yang, Yanqing; Dong, Hongming; Luo, Qin; Chen, Zhen; Du, Haijun; Mei, Guoyong; Wang, Xinyue; Guan, Yake; Zhao, Chihong; Han, Jun; et al. (Frontiers in Public Health, 2024)
Objective: To study the molecular epidemiology and clinical characteristics of Respiratory syncytial virus (RSV) infection from hospitalized children with ARTI in Bengbu.Methods: 124 nasopharyngeal swab specimens and clinical data from children with ARTI cases were collected in Bengbu, China during winter 2021-2022. The samples were detected by qPCR of 13 respiratory viruses. Phylogenetic analysis was constructed using MEGA 7.0. All analyses were performed using SAS software, version 9.4.In winter 2021-2022, URTI, NSCAP, SCAP, and bronchiolitis accounted for 41.03%, 27.35%, 17.09%, and 14.53% of hospitalized children in Bengbu, China. The detection rates of top three was RSV(41.94%), ADV(5.65%), FluB (5.65%) in hospitalized children through 13 virus detection. RSV is the main pathogen of hospitalized children under 2 years old. 48 sequences of G protein of RSV were obtained through PCR amplification, including RSV-A 37 strains and RSV-B 11 strains. Phylogenetic analysis showed that all RSV-A and RSV-B were ON1 and BA9 genotype, respectively. ON1 genotype were further divided into two clades. The majority of ON1 strains formed a unique genetic clade with T113I, V131D, N178 G, and H258Q mutation. Furthermore, RSV infection was an independent risk factor for ventilator use (OR=9.55, 95% CI 1.87-48.64).Conclusions: There was a high incidence of RSV among hospitalized children during winter 2021-2022 in Bengbu with ON1 and BA9 being the dominant strains. This study demonstrated the molecular epidemiological characteristics of RSV in children with respiratory infections in Bengbu, China.